Significant delay and decreased chance of treatment for acute ischemic stroke patients on remote outer islets of China compared with the main island: the PUTUO Study - Bangbo Xia; Ning Liu; Li Hu; Hongyi Zhu; Bifeng Zhong; Zhongheng Zhang; Jian Lin; Yong Kang (James Cook University, 2023)
Introduction: Data from acute ischemic stroke patients throughout 2021 from one district of an archipelago city of China were collected and analyzed retrospectively to determine the management difference due to time lags from onset of symptoms to the arrival at the stroke center (FMCT) of two regions: main island (MI) and outer islets (OIs). Methods: All patients information from 1 January to 31 December 2021 was retrieved through the electronic medical records system of the only stroke center in MI. After screening and exclusion, each patient's medical record was reviewed by two neurologists separately. Before OI patients were allocated to a group, their residential addresses at onset of the stroke were confirmed by telephone. Comparisons were analyzed between the two regions for gender, age, pre-stroke risk factors and peri-admission management parameters. Results: A total of 326 patients met the inclusion criteria: 300 from the MI group and 26 for the OI group. Intergroup comparisons for gender, age and most of the risk factors showed no significant difference. FMCT were shown to be significantly distinct (p<0.001). Hospitalization expenses also showed significant difference. The odds ratio of the definite treatment IV thrombolysis was 0.131 (OI group to MI group range: 0.017-0.987, p=0.021). Conclusion: The diagnosis and treatment of acute ischemic stroke patients from OIs was significantly postponed compared to those from MI. Therefore, new effective and efficient solutions are urgently needed.